2007
DOI: 10.1002/yea.1478
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tea tree oil and antifungal agents on a reporter for yeast cell integrity signalling

Abstract: Cell integrity in Saccharomyces cerevisiae is ensured by a rigid cell wall whose synthesis is controlled by a highly conserved MAP kinase signal transduction cascade. Stress at the cell surface is detected by a set of sensors and ultimately transmitted through this cascade to the transcription factor Rlm1, which governs expression of many genes encoding enzymes of cell wall biosynthesis. We here report on a number of versatile reporter constructs which link activation of a hybrid, Rlm1-lexA, by the MAP kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 69 publications
1
30
0
2
Order By: Relevance
“…However, the reduction of stiffness caused by this drug is lower than that after ethanol stress, indicating some difference in the mechanism. It is possible that in contrast to the effects of ethanol, this effect is in part counterbalanced by the activation of the CWI pathway, since it was reported by Straede et al (97) that AmB as well as other plasma membrane-interfering compounds, such as chlorpromazine and nystatin, caused an activation of this pathway. However, and in accordance with our model, it can be expected that any stretching of the plasma membrane caused, for instance, by an increase of the turgor pressure or by some organic solvents (98) might also alter the stiffness of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reduction of stiffness caused by this drug is lower than that after ethanol stress, indicating some difference in the mechanism. It is possible that in contrast to the effects of ethanol, this effect is in part counterbalanced by the activation of the CWI pathway, since it was reported by Straede et al (97) that AmB as well as other plasma membrane-interfering compounds, such as chlorpromazine and nystatin, caused an activation of this pathway. However, and in accordance with our model, it can be expected that any stretching of the plasma membrane caused, for instance, by an increase of the turgor pressure or by some organic solvents (98) might also alter the stiffness of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The induced conformational changes could then be transmitted to the cytoplasmic tails, allowing the intracellular response to be triggered. Several observations support this hypothesis: (a) drugs affecting either the cell wall polysaccharide composition (such as Calcofluor white and Congo red) or the plasma membrane (such as chlorpromazine or tea tree oil) have been shown to activate the CWI pathway [50]; (b) mutants with a defective O-mannosylation of the sensors (and of other secreted cell wall proteins) display the typical cell lysis phenotypes of CWI pathway mutants [32]; (c) biophysical evidence from determination of the mechanics of single molecules measured in vivo by atomic force microscopy (AFM) suggests that the STR region confers a nanospring structure to the Wsc1 sensor, consistent with a rigid connection between the TMD and the CRD [9]. In fact, the authors found that a lower degree of mannosylation or the insertion of non-mannosylated glycine residues within the STR region abolished the nanospring properties.…”
Section: Sensor Structure and Mechanicsmentioning
confidence: 98%
“…Yeast strains with a wsc1 deletion are temperature-sensitive and hypersensitive to drugs interfering with the cell wall (Calcofluour white, Congo red or glucan synthase inhibitory echinocandins, such as Caspofungin) or with the plasma membrane (chlorpromazine and tea tree oil [22,50]), whereas wsc2 and wsc3 single and double deletions are hardly affected [55,61]. On the other hand, mid2 deletions are hypersensitive to pheromone treatment and hyperresistant to Calcofluor white and tea tree oil [42,50]. It was proposed that Wsc1 would act primarily during vegetative growth, whereas Mid2 would be more involved in the mating response, with some functional overlap [42].…”
Section: Sensor Distribution and Dynamicsmentioning
confidence: 99%
“…Böylece bu maddeler su ile hücreye girer, hücre membranının stabilizasyonunu bozmaktadır ve olay akışı osmotik şok ile sonuçlanmaktadır. 58 …”
Section: çAy Ağaci Yaği(tea Tree Oġl)unclassified